A decade of Shifting Trends, Themes, and Trajectories in Linguistics Studies - Yaqin, Lalu Nurul (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
The trend topics plot identifies emerging and popular research areas over the years, with a clear rise in themes related to Computational Linguistics, machine learning, language models, and natural language processing. The USA, China, and the United Kingdom are leading in contributions, with significant publications in journals like